Secret intelligence in the European states system, 1918-1989 - Haslam, Jonathan; Urbach, Karina (Stanford University Press, 2014)
This volume brings together a collection of essays that analyse the recent evidence concerning the history of the European states system of the last century. The essays offer an array of insight across countries and across time. Together they highlight the critical importance of the prevailing domestic circumstances - technological, governmental, ideological, cultural, financial - in which intelligence operates.